Strategi Peningkatan Motivasi Kerja Guru Melalui Kepemimpinan Kepala Sekolah Yang Profesional Dan Komunikasi Internal Yang Efektif Di SMK Negeri 2 Wewewa Barat Tahun Pelajaran 2021/2022 - Yosias Malo (CV. Multi Kreasi Media, 2023)
This research aims to investigate the influence of the professionalism of the school principal's leadership and internal communication on teachers' work motivation at SMK Negeri 2 Wewewa Barat for the Academic Year 2021/2022. This study employs an action research model conducted in two cycles, with each cycle comprising four stages: planning, implementation, evaluation, and reflection. The subjects of this study are the teachers at SMK Negeri 2 Wewewa Barat, totaling 53 individuals. The research results indicate that during the pre-cycle stage, the number of teachers who achieved passing grades was 21 individuals (39.62%). After implementing the model of professional leadership and internal communication in Cycle I, the number of passing teachers increased to 32 individuals (60.38%), and in Cycle II, it further rose to 47 individuals (88.68%). This data demonstrates a positive influence of the professionalism of the school principal's leadership and internal communication model in enhancing the work motivation of teachers at SMK Negeri 2 Wewewa Barat for the academic year 2021/2022. The continuous implementation of school action research can enhance the quality of the school principal's leadership professionalism, internal communication effectiveness, and teacher work motivation at SMK Negeri 2 Wewewa Barat. Consequently, it can be concluded that the implementation of school action research at SMK Negeri 2 Wewewa Barat provides benefits in improving the quality of the school principal's leadership professionalism, internal communication effectiveness, and teacher work motivation, ultimately leading to an enhancement in the quality of education at SMK Negeri 2 Wewewa Barat.